Pile end bearing capacity in rock mass using cavity expansion theory - Haythem Gharsallaoui; Mustafa Jafari; Alain Holeyman (Journal of Rock Mechanics and Geotechnical Engineering, 2020)
Much empiricism is involved in design of rock-socketed piles in rock masses. In light of this, an analytical solution based on the cavity expansion theory is proposed for calculating the ultimate bearing capacity at the tip of a pile embedded in rock masses obeying the Hoek-Brown failure criterion. The ultimate end bearing capacity is evaluated by assuming that the pressure exerted at the boundaries of a pressure bulb immediately beneath the pile tip is equal to the limit pressure required to expand a spherical cavity. In addition, a relationship is derived to predict the pile load-settlement response. To demonstrate the applicability of the presented solution, the results of this study were compared to those of 91 field tests from technical literature. Despite the limitations, it is found that the end bearing resistance computed by the present work is in good agreement with the field test results.